Initial Public Offerings (IPOs): A Boon or a Bane? - Trivedi, Jigna; Soni, Bindiya (Indian Journal of Finance, 2012)
IPOs are the most favoured tool adopted by corporates to raise money from the general public. An IPO is the first sale of stock by formerly a private company. The revolutionary reform which took place in the Indian stock market was fair price discovery of IPOs through the book building mechanism. The present paper tries to comprehend the concept of the book built issue, its importance and advantages over the Fixed Price Regime. The paper also tries to bring forth the short term return available to the subscribers of IPOs. The concept of listing gains and intra day gains are studied with respect to short term investors. IPOs issued in the duration of five years, starting from 2006 to 2010 were taken as a base for computing the return and for commenting on the performance of IPOs. Overall, the reasons for high and low performance of IPOs are discussed in the paper. As a part of the study of pre - subscription of IPOs, the paper highlights the importance of IPO grading to be used as a tool to learn about the fundamentals of the company. The paper highlights the quantum of listing gains derived by the investors on listing of the IPOs.